Skład ciała dzieci w wieku 8-13 lat w zależności od ich urodzeniowej masy ciała = Body composition of childrenaged 8-13 inrelationto their birth weight - Rzeszotek, Mariusz; Rynkiewicz, Mateusz; Rzeszotek, Klaudia; Rynkiewicz, Tadeusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Knowledge on the influence of birth dystrophy on the whole body composition and its segments in the later stages of ontogeny is ambiguous. There is also little information on forming the indicators of the body fat mass index (FFMI) and the fat free mas index (BFMI) in dystrophic children. Therefore, differences in the whole body composition and its segments as well as the BFMI and FFMI values were determined in children aged 8-13 depending on their birth weight. The following hypotheses were put forward: 1. Birth dystrophy significantly affects body composition in children aged 8-13; 2. The BFMI and the FFMI are useful indicators of controlling the physical development in children with different birth weight.
Keywords: skład ciała; dziecko; urodzeniowa masa ciała; body composition; child; birth weight